Statistical Modeling and Kinetic Studies on the Adsorption of Reactive Red 2 by a Low-Cost Adsorbent: Grape Waste-Based Activated Carbon Using Sulfuric Acid Activator-Assisted Thermal Activation - Seyyed Alireza Mousavi; Davood Shahbazi; Arezoo Mahmoudi; Parviz Mohammadi; Tooraj Massahi (Adsorption Science & Technology)
The efficiency of activated carbon produced from grape waste as a low-cost, nontoxic, and available adsorbent to remove Reactive Red 2 from aqueous solution has been investigated. The prepared activated carbon has been characterized by FTIR, SEM, and BET. The results of characterization indicate the successful conversion of grape waste into mesoporous AC with desirable surface area consist of different functional groups. The results of statistical modeling displayed high R2 value of 0.97% for dye removal that shows the developed model has acceptable accuracy. The effect of independent variables indicated that the highest adsorption (96.83%) obtained at pH 3, adsorbent dosage of 12.25 g/L, and initial dye concentration of 100 mg/L when the adsorption time was 90 min. The results of isotherms modeling showed that the data fit well with the Langmuir (type II). The kinetic studies using pseudofirst-order and pseudosecond-order models pointed out that the type (I) of pseudosecond-order kinetic model provided the best fit to the adsorption data. Parameters of thermodynamics including Gibbs energy (ΔG°) and ko were calculated. The values of ΔG° indicated that the dye adsorption of RR2 is spontaneous. The agricultural wastes due to special points such as low-cost, availability, and high ability to produce an adsorbent with high efficiency to remove dye can be proposed for water and wastewater treatment.